MENAVIGASI TABIR PELANGGARAN SHARIAH COMPLIANCE: PERAN LITIGASI DALAM MENJAGA INTEGRITAS PERBANKAN SYARIAH - Aida Jasmine Nur Riyadi; Suwarsit Suwarsit (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Islamic banking in Indonesia is experiencing rapid growth, but accompanied by potential violations of sharia principles. Litigation plays an important role in maintaining the integrity of Islamic banking by enforcing sharia law and providing legal certainty for the parties. The role of litigation in navigating the veil of sharia compliance violations in Islamic banking. First, it discusses the scope of sharia compliance violations, including usury practices, contract manipulation, and other violations of sharia principles.Second, it discusses the role of litigation in enforcing sharia law. This includes dispute resolution mechanisms through religious and public courts, as well as the role of the National Sharia Council in providing fatwas and directions related to the application of sharia law in Islamic banking.Third, it was discussed about the role of litigation in providing legal certainty for the parties. This includes legal certainty for customers, Islamic banks, and regulators. This legal certainty is important to build public trust in Islamic banking and encourage its sustainable growth. This abstract concludes that litigation is an important instrument in maintaining the integrity of Islamic banking. By enforcing sharia law and providing legal certainty, litigation can help build fair, transparent, and accountable Islamic banking